2011
DOI: 10.1080/10826076.2011.593069
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive HPLC Method With Fluorescence Detection and on-Line Wavelength Switching for Simultaneous Determination of Valsartan and Amlodipine in Human Plasma

Abstract: & This study describes the development and validation of a highly sensitive high-performance liquid chromatographic method with fluorescence detection and on-line emission wavelength switching for the simultaneous determination of valsartan (VAL) and amlodipine (AML) in human plasma. Irbesartan (IRB) was used as internal standard (IS). VAL, AML, and IRB were isolated from plasma by nonextractive procedure; simple protein precipitation with methanol. Separations were performed in low pressure gradient mode on H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…18 For VAL, UV spectrophotometry, [19][20][21][22] HPLC, 19,23 and HPTLC 24 methods were reported. Published methods for simultaneous determination of AMD and VAL include UV spectrophotometric, [25][26][27][28][29][30][31][32][33][34][35][36] spectrofluorimetric methods [37][38][39] , HPLC, 25,30,31,[40][41][42][43][44][45][46][47] TLC 44,48 and capillary electrophoresis. 49,50 The present research work is concerned with the development of two simple, accurate and sensitive spectrophotometric methods: absorption correction method (ACM) and dual wavelength method (DWM) for simultaneous determination of AMD and VAL with no need for prior separation.…”
Section: Introductionmentioning
confidence: 99%
“…18 For VAL, UV spectrophotometry, [19][20][21][22] HPLC, 19,23 and HPTLC 24 methods were reported. Published methods for simultaneous determination of AMD and VAL include UV spectrophotometric, [25][26][27][28][29][30][31][32][33][34][35][36] spectrofluorimetric methods [37][38][39] , HPLC, 25,30,31,[40][41][42][43][44][45][46][47] TLC 44,48 and capillary electrophoresis. 49,50 The present research work is concerned with the development of two simple, accurate and sensitive spectrophotometric methods: absorption correction method (ACM) and dual wavelength method (DWM) for simultaneous determination of AMD and VAL with no need for prior separation.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods to determine simultaneously AML and VAL in pharmaceutical formulations and biological fluids have been reported in the literature, including those capillary electrophoresis [3], chromatography [4][5][6][7][8][9][10], spectrofluorimetry [11], and spectrophotometry [12,13]. Some of these methods, such as chromatography and spectrophotometry, require a prior separation steps and tedious analytical process during analysis, the use of organic solvents, thereby generating high amounts of waste, time-consuming derivatization steps and high implementation costs, thus justifying the need for reliable, low cost and simpler methods.…”
Section: Introductionmentioning
confidence: 99%
“…3 Minoxidil is used to control blood pressure by relaxing and dilating the blood vessels, and it is always used in combination with beta-blockers and diuretics in order to prevent its side effects. 4 Several analytical techniques such as High Pressure Liquid Chromatography (HPLC), 5,6 Liquid Chromatography-Mass Spectrometry (LC-MS), 7,8 uorescence, 9,10 electrochemical, 11,12 and UV-visible spectroscopy 13,14 are reported for the analysis of two vasodilator drugs (amlodipine besylate and minoxidil) in pure pharmaceutical formulations and tablets. Unfortunately, these methods require more time for analysis, expensive instrumentation, and moreover, their applicability is limited only to the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…However, expensive fabrication, complex measurement setup, and sample preparation with remarkably sophisticated functionalization is required. Whereas, X-band (8)(9)(10)(11)(12) GHz) metamaterial sensor demonstrated by Lee and co-authors for specic binding between prostate-specic antigen (PSA) and antibody showed LOD up to 1 ng mL À1 . 28 Since the majority of the investigated microwave sensor devices are planar, in situ analysis cannot be performed into various biological and chemical assays.…”
Section: Introductionmentioning
confidence: 99%